A call for refining the peatland restoration strategy in Europe. Issue 11 (5th September 2022) - Zak, Dominik; McInnes, Robert J.
Abstract: Substantial amounts of money have been invested in peatland restoration over the last decades to address the current challenges of global changes and to enhance biodiversity. Given the magnitude of financial investments and the pressing societal needs, it is essential that appropriate decisions are made about the restoration techniques employed to avoid negative consequences and to optimise the benefits to human society. Based on the knowledge and expertise that has been developed over recent decades, three approaches to peatland restoration are discussed regarding their implications for climate change, nutrient fluxes and biodiversity: peatland inundation, topsoil removal and slow rewetting. Considered over the long term, for instance tens or hundreds of years, rewetted peatlands have the potential to fulfil multiple restoration goals, including those targeting climate change mitigation, water quality protection and species conservation. In short term, ill‐informed decisions on the approach to peatland restoration can generate negative impacts, for instance on the downstream water quality or radiative forcing gas emissions. Synthesis and application . The restoration of peatlands, and the trajectory that any restorative action may take, is a matter of societal choice; however, it is essential that society understands the broad potential benefits and disadvantages that such restoration may have so that evidence‐based choices can be made. Abstract : The restoration of peatlands, and the trajectory that any restorative action may take, is a matter of societal choice; however, it is essential that society understands the broad potential benefits and disadvantages that such restoration may have so that evidence‐based choices can be made. Resume: Igennem de seneste årtier er der investeret betydelige beløb i genopretning af tørvejorder for at adressere de globale forandringer og øge biodiversiteten. Set i lyset af omfanget af disse investeringer og samfundets presserende behov for at mindske udledningen af drivhusgasser er det af afgørende betydning, at valget af genopretningsmetoder er baseret på tilstrækkelig viden for at optimere udbyttet og undgå negative sideeffekter. Baseret på den viden og ekspertise, som er blevet opbygget igennem de seneste årtier, er særligt tre genopretningsmetoder samt deres implikationer for klimaforandringer og næringsstofudvaskning genstand for diskussion: oversvømmelse af tørvejorder, fjernelse af topjord og langsom vådlægning. Set i et langt tidsperspektiv (årtier til århundreder) kan vådlagte tørvejorder potentielt opfylde flere målsætninger, herunder modvirke klimaforandringer, bevare og forbedre vandkvaliteten samt bevarelse af dyrearter. På kortere sigt kan genopretninger, som ikke er udført på optimalt vidensgrundlag, medføre øget drivhusgasudledning og/eller forringelse af vandkvaliteten nedstrøms. Sammenfatning og anvendelse. Genopretningen af tørvejorder, og det fremtidige forløb, som disse genopretningstiltag måtte have, afhænger af samfundsmæssige beslutninger. Det er derfor helt essentielt, at samfundet er oplyst om det brede spektrum af potentielle fordele og ulemper ved de forskellige genopretningsmetoder, således at der kan træffes optimale og evidensbaserede beslutninger.